1997
DOI: 10.1039/a608342k
|View full text |Cite
|
Sign up to set email alerts
|

Persistent oxidation dications of dialkyl- and tetraalkyl-perylenes and dibenzo[cd,lm]perylene; charge distribution mode, substituent effects and conformational aspects

Abstract: Starting with appropriate alkylnaphthalenes , 3,10-dimethyl-2, 3,10-diethyl-3, 2,3,10,11-tetramethyl-4 and 3,4,9,10-tetramethyl-perylene 5 were synthesized by a sequence of radical cation and radical anion coupling steps. Persistent oxidation dications of parent perylene 1, alkylperylenes 2-5 and dibenzo[cd,lm]perylene 6 were generated in SbF 5 -SO 2 ClF. Based on 1D-and 2D-NMR experiments combined with AMl calculations the charge delocalization mode in the dications was deduced. The total deshielding ( 13 C)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…55 Alkylperylene dications by twoelectron oxidation with SbF 5 /SO 2 ClF were observed in lowtemperature 13 C NMR. 56 Synthesis of 3,9-or 3,10-dibromoperylene was reported in the literature.…”
Section: +mentioning
confidence: 99%
“…55 Alkylperylene dications by twoelectron oxidation with SbF 5 /SO 2 ClF were observed in lowtemperature 13 C NMR. 56 Synthesis of 3,9-or 3,10-dibromoperylene was reported in the literature.…”
Section: +mentioning
confidence: 99%
“…28 In our previous studies, we reported on dications from a series of alkyl(cycloalkyl)pyrenes 20 and on alkylperylenes. 19 In relation to our continuing interest in arenium ions and dications derived from different classes of PAHs and the significance of electrophiles derived from carcinogenic PAHs in adduct formation with DNA bases that could lead to cell damage, we report here the first examples of benzo[a]pyrenium dications, 2-6, and pyrenium dications, 7-9. Detailed assignments for parent 1 are also included for comparison.…”
Section: Introductionmentioning
confidence: 99%
“…Following initial feasibility studies using early, low-field 1 H NMR by Brouwer, 12 many of the subsequent investigations were reported by Olah and associates. [13][14][15][16][17] More recent examples were provided by Michl, 18 Laali, [19][20][21][22] Mu ¨llen, 8,9 and their associates; the topic has been reviewed. 23 Because of the well-established relationship between 13 C NMR chemical shift and charge in structurally analogous ions, it became the primary tool for probing dications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 Our product was further characterized as quaterrylene by a novel NMR technique. The well-known insolubility of high melting crystalline substances such as 4 suggests that NMR spectral characterization should be impossible; however, many arenium ions and arene oxidative dications 38,39 (neutral structure minus two electrons) have been observed in solution [40][41][42][43][44][45][46][47] and we investigated whether protonation might increase solubility and facilitate NMR analysis. Quaterrylene ( 4) is insoluble in dichloroethane (DCE), but with the aid of mild sonication (Scheme 2), we find that small amounts dissolve in 1 M triflic acid-d/DCE-d 4 with formation of a dark blue-green solution.…”
mentioning
confidence: 99%